2020
DOI: 10.1109/access.2020.2972130
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network-Based Prediction Model for Passenger Flow in a Large Passenger Station: An Exploratory Study

Abstract: As the hub and carrier to transfer the passengers, the railway station is an important factor that affects the rail passenger transportation because the normal operation of the station without load redundancy is determined by the moderate passenger flow. It means reasonable and accurate prediction of passengers entering and leaving the station can provide the basis and guarantee for the station security, the resources allocation and the personnel deployment. Since the neural network model is good at processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Throughout the years from 1970 to 1980, perceptronlike neural networks that utilized approximation of nonlinear functions operated with an integral of multilayer neurons and nonlinear signal processing. A significant research extension has accomplished in this specific domain, and the results included successful determinants of using neural networks for prediction [15][16].…”
Section: A Artificial Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the years from 1970 to 1980, perceptronlike neural networks that utilized approximation of nonlinear functions operated with an integral of multilayer neurons and nonlinear signal processing. A significant research extension has accomplished in this specific domain, and the results included successful determinants of using neural networks for prediction [15][16].…”
Section: A Artificial Neural Networkmentioning
confidence: 99%
“…By simplifying ( ) = ( 2 ), the argument of ψ is the squared norm, which is more pleasurable to differentiate, and the result shows in Eqn. (16).…”
Section: ) Activation Functionsmentioning
confidence: 99%
“…Secondly, the current railway operation management still relies on the experience of dispatchers to judge the change of passenger flow [2] , which results in the lack of ability and preparation of some railway departments to deal with major public health emergencies such as new coronary pneumonia, and it is difficult to adapt to the passenger flow. Fluctuation characteristics [3] . Therefore, it is necessary to study the short-term passenger flow forecasting of railway emergencies to provide theoretical basis for operation management.…”
Section: Introductionmentioning
confidence: 99%
“…When the studies in the literature are examined in the light of all this information, many studies on rail passenger transport (Baumol, 1975;Due, 1997;Jing and Yin, 2020;Kulbovskyi et al, 2019) and air passenger transport (de Oliveira Dias, 2019; Demirhan et al, 2021;Goetz, 1992;Moura et al, 2020;Oleshko and Heiets, 2018;Wolle, 2021;Yang et al, 2018) have been found. Although there are studies using different methods that examine the two modes of transport together (Albalate et al, 2015;Chen, 2017;Clewlow, 2012;Erdogan et al, 2020;Grimme, 2007;Pagliara et al,.…”
Section: Introductionmentioning
confidence: 99%